Characterization of ceramides with phytosphingosine backbone by hydrogen-deuterium exchange mass spectrometry - Đapić, Irena (Array, 2019)
Ceramides are a lipid subclass of the sphingolipids that show large structural diversity. Structural characterization of the ceramides (CERs) can lead to better understanding of their role and function in the biological system. Here we investigated representatives of NP (CER III, CER IIIB) and AP ceramide classes (CER VI) that contain phytosphingosine (P) backbone. Ceramides were characterized in positive ionization mode by hydrogen-deuterium exchange mass spectrometry (HDX-MS). Fragmentation in positive ionization mode of the CER III and CER VI resulted in abundant ions assigned to phytosphingosine moiety at m/z 282, 300 and 318. HDX-MS of fragments showed increase in m/z of corresponding ions confirming the exchange of deuterium. In negative ionisation spectra multiple fragment ions were assigned to fatty acyl (RCOO–) moiety. Presence of RCOO– allowed unambiguous identification of CER III and CER IIIB which were distinguished by the presence of double bond on fatty acyl chain.